Analysis of Plastic Flow Localization in Bimetal Electrolytically Saturated with Hydrogen - Barannikova, S; Li, Yu.; Malinovskiy, A; Zuev, L (International Journal of Engineering and Technology, 2018)
Plastic deformation of bimetal compound of austenitic stainless and low-carbon construction steels, resistant to corrosion, is localized through the digital image correlation method upon the uniaxial tension of sample. The evolution of zones of plastic deformation in bimetal is inspected upon the onset of the process and is exposed to hydrogen saturation in a three-electrode electrochemical cell at a controlled constant cathode potential for 6 hours. Localized plastic deformation zones are found to form and evolve during the tension of bimetal samples both at the onset and after 6 hour of the electrolytic hydrogenation throughout the plastic yielding in the primary, protective and transitional layers of the bimetal. The bimetal fracture is initiated by stress concentrated in the bimetal transition layer. Nucleation and propagation of a crack is observed at early work-hardening stages. The fracture of bimetal after hydrogenation is established to be more ductile as compared with precursor.Â Â